Accommodating persons with communication disabilities in court: Perspectives of law students - Juan Bornman; Dianah Msipa (African Journal of Disability, 2024)
Background: Individuals with communication disabilities encounter obstacles in attaining equal access to justice compared to others. Despite experiencing widespread violence and abuse, they come across as challenges in seeking remedies through the legal system. One barrier is the lack of awareness among legal practitioners regarding suitable accommodations that would facilitate effective participation in court for individuals with communication disabilities.